If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * 3 + -7x + 4 = 0 Reorder the terms for easier multiplication: 3x + -7x + 4 = 0 Reorder the terms: 4 + 3x + -7x = 0 Combine like terms: 3x + -7x = -4x 4 + -4x = 0 Solving 4 + -4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -4x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -4x = 0 + -4 -4x = 0 + -4 Combine like terms: 0 + -4 = -4 -4x = -4 Divide each side by '-4'. x = 1 Simplifying x = 1
| 0.09x^2-30x+600=0 | | 100+5+5x=180 | | 15-m=24 | | 3x+42+90=180 | | (2.5-z)/(2.5-1)=0.06 | | (x+y)+(x+y)+(x+y)= | | (10+11*-1)+3(4*-1+3)= | | (10+11*-1)+3(4*-1+3)=2 | | -4.6y-2(2.2y-7.2)=-2.1(y-20) | | 5y-1-3y=5.20 | | 7y(2x-5y)= | | (7a+7b)+(6a-8b)= | | x+3-2x=5+2x-3x | | 5-5x-2x=4 | | -10=25+3x | | 2x+3n+7=-43 | | (2a+5b)+(5a+2b)+(6a-8b)= | | 4910x+10=24 | | (2a+5b)+(5a+2b)= | | Ln(y)=5x+c | | Ln(4t)-ln(3t^2)=2 | | 0=b^2-6b+10 | | 3x-3-x+2x=x+3x-5 | | X+5y=153x+2y=41 | | 5x+4y=13.2 | | X+2x+y-5=100 | | Y=4.8-2x | | -x+15=-17 | | m/-7-24=2 | | 3-0.5x=1.8 | | -x=-390 | | x+3x=5+3 |